In Vitro Management of Post-harvest Spoilage Pathogens of Mango (Journal of Plant Disease Sciences, 2019)
The effect of fungicides, chemical, oils, wax and bio-agent against postharvest spoilage of mango was evaluated for their inhibitory effect in vitro. After 24 hours, carbendazim @ 0.1 per cent was found superior in inhibiting the conidial germination (87.50%) of C. gloeosporioides after 48 hours, it was (83.74%), after 72 hours, highest was in (78.05%) recorded. After 24 hours, carbendazim @ 0.1 per cent was effective in restriction (89.03%) of conidial germination of Alternaria alternata at 48 hours inhibition was (82.54%), recorded and after 72 hours inhibition was (74.92%) observed. Highest conidial inhibition of Aspergillus niger found in carbendazim @ 0.1 per cent was (91.66%), (86.52%) and (82.87%) after 24, 48 and 72 hours respectively.
Keywords: Mango; post harvest; pathogens; fungicides; oils